Distribution of opinions on what sport related themes should replace live sports on television (TV) during the COVID-19 pandemic - Lange, D. (Statista, 2020)
Just one of the unprecedented impacts of the COVID-19 pandemic is the widespread cancellation of virtually all live sports coverage, as leagues and competitions are postponed or cancelled.